Preparation of novel RGD-conjugated thermosensitive mPEG-PCL composite hydrogels and in vitro investigation of their impacts on adhesion-dependent cellular behavior - Kim, Hyun Joo; You, Su Jung; Yang, Dae Hyeok; Chun, Heung Jae; Kim, Moon Suk (Journal of Industrial and Engineering Chemistry, 2020)
The arginine–glycine–aspartic acid (RGD) motif plays a critical role in cell-extracellular matrix (ECM) interactions through focal adhesion, which may orchestrate various aspects of cellular behaviors for development and maintenance of tissues. Here, we prepared novel thermosensitive hydrogel systems comprising methoxy polyethylene glycol-b-polycaprolactone (MP) and RGD-conjugated MP (MP-RGD) with various RGD contents (MP/MP-RGD) based on our recently patented technology. The conjugation of RGD to MP through biomolecular nucleophilic substitution was qualitatively and quantitatively assessed using 1H nuclear magnetic resonance (NMR) spectroscopy and the Sakaguchi assay, respectively. The sol–gel–sol transition with increasing temperature was confirmed using viscoelastic measurements together with tilting tests. In vitro experiments using bone marrow-derived mesenchymal stem cells (BMSCs) revealed that MP/MP-RGD hydrogels significantly enhanced expression of integrins (α2, α5, and β1) and facilitated formation of focal adhesions (increased expression of FAK, focal adhesion kinase) that lead to cytoskeletal reorganization through integrin-mediated cell signaling. Real-time polymerase chain reaction (PCR) array also showed upregulation of signaling genes involved in the receptor tyrosine kinase (RTK) signaling cascade such as mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK) for growth factors and phosphoinositide 3-kinase (PI3K) and AKT (protein kinase B) for survival factors. This suggests that extensive crosstalk pathways exist between integrins and RTKs, which was confirmed through western blotting. Consequently, MP/MP-RGD hydrogels showed a significantly increased BMSC proliferation rate with increasing RGD content of the samples.
Keywords: BMSCs; Focal adhesions; In-situ forming; Integrins; Thermo-sensitive hydrogel; BMSCs; Focal adhesion; In situ-forming hydrogel; Integrin; RGD; Thermosensitive hydrogel